Jaw pain secondary to atypical maxillary torus near the incisive canal: A cone beam computed tomography study - Anthony Albert; Mel Mupparapu (Wolters Kluwer Medknow Publications, 2018)
Pain in the anterior maxilla can be odontogenic or nonodontogenic. If it is not related to the teeth, then the differential diagnosis is based on a clinical exam, radiographic exam, and often, on advanced imaging. This case report is based on a 58-year-old male with a chief complaint of chronic pain with acute exacerbations in the region of the rugae of the maxillary central incisors. Clinical examination and planar radiography led to the suspicion of a cyst in the region of the incisive foramen. The patient was referred for advanced imaging. Cone beam computed tomography imaging confirmed the presence of an unusual tori in the region of the incisive foramen that led to periodic inflammation in the region. A differential diagnosis of the pain included pain secondary to a localized inflammation of the incisive canal and nasopalatine duct, and an inflammation of the soft tissue interdental col in the region of the central incisors as well as the benign and malignant minor salivary gland tumors. Because the rugae is attached to the palate, any expansion of the soft tissues in this region causes pain that must be diagnosed accurately to treat the cause.